Endemic Cyprus Scops Owl Otus cyprius Readily Breeds in Artificial Nest Boxes - Iezekiel, Savvas (Animals (Basel), 2021)
SIMPLE SUMMARY: Nest boxes are considered a valid conservation tool in order to sustain wild populations of birds. The Cyprus Scops Owl was recently defined as a new species. However, the extant information on the species is sporadic and the population level is not confirmed. In order to evaluate the ability of the species to use nest boxes, and to understand its habitat preferences, we placed boxes in rural areas, at the forest edge, and in the Paphos Forest. We found that the Cyprus Scops Owl displayed a preference for the forest edge and rural areas; although we also had, several pairs occupy nest boxes in the forest. We show that the nest box strategy can be implemented if in the future the species is threatened. ABSTRACT: As is well-known, endemic island bird species are especially vulnerable to extinction from anthropogenic environmental change and reduced fitness compared with mainland taxa. The Cyprus Scops Owl, Otus cyprius, is a recently recognized island endemic species whose ecology and breeding biology have not been studied. It nests mainly in holes in trees and buildings, so the felling of old trees, modern architectural practices, and the renovation of old houses in villages may reduce nest site availability. Its population trend is also unknown. Therefore, to better determine its ecological requirements and habitat preferences we placed nest boxes in rural areas adjacent to the forest, in the forest, and in the ecotone between them, and used breeding success as our indicator of habitat suitability. We found that breeding parameters like laying date, clutch size, length of the incubation period, hatching day, hatching success, and number of nestlings did not differ between the three habitats. Despite the low level of nest box occupancy rate (5–11%) the endemic Cyprus Scops Owl readily breeds in artificial nests. Therefore, although we are unaware of any current threats to the Cyprus Scops Owl, we recommend that its conservation be prioritized, including studies, monitoring, habitat conservation, and the provision of nest boxes.